2018
DOI: 10.1038/s41598-018-27225-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antimicrobial activity and conformational analysis of the class IIa bacteriocin pediocin PA-1 and analogs thereof

Abstract: The antimicrobial peptide pediocin PA-1 is a class IIa bacteriocin that inhibits several clinically relevant pathogens including Listeria spp. Here we report the synthesis and characterization of whole pediocin PA-1 and novel analogs thereof using a combination of solid- and solution-phase strategies to overcome difficulties due to instability and undesired reactions. Pediocin PA-1 thus synthesized was a potent inhibitor of Listeria monocytogenes (MIC = 6.8 nM), similar to the bacteriocin produced naturally by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 72 publications
7
50
0
Order By: Relevance
“…(C) Peptide-membrane interaction. Peptide 6 (light blue)with membrane bonding residues and potential receptor binding residues colored in cyan and red respectively.CONCLUSIONAs previously observed with pediocin PA-1 analogs,43 the use of linear bactofencin A in biological medium yielded the same activity as the native cyclic counterpart. Modifications such as C-terminal amidation and replacement of the methionine residues with leucine allowed a fourfold increase in inhibitory activity against S. aureus.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…(C) Peptide-membrane interaction. Peptide 6 (light blue)with membrane bonding residues and potential receptor binding residues colored in cyan and red respectively.CONCLUSIONAs previously observed with pediocin PA-1 analogs,43 the use of linear bactofencin A in biological medium yielded the same activity as the native cyclic counterpart. Modifications such as C-terminal amidation and replacement of the methionine residues with leucine allowed a fourfold increase in inhibitory activity against S. aureus.…”
supporting
confidence: 75%
“…bacteriocins can be very challenging since the presence of several features essential for their bioactivity, such as lasso structure, large macrocycles, lanthionines, glycosylated side chains or complicated peptide motifs can make the task very daunting. 42 showing the same activity, 43 no disulfide bond formation was performed and the linear analogs 7-18 used as is in the antimicrobial assays. Figure S5).…”
Section: Synthesis Of Bactofencin a And Analogs Thereof The Chemicalmentioning
confidence: 99%
“…As expected, pediocin displayed activity only against L. coryniformis with EC 50 of 3 nM. This is in approximate agreement with published potency pf pediocin PA-1 and related bacteriocins (2527).…”
Section: Resultssupporting
confidence: 90%
“…Our data, support and co-operate with the result of Patil, has contributed new scientific information to the pediocin antimicrobial spectrum data bank. Besides, recombinant pediocin did not display activity against Staphylococcus aureus and Bacillus subtilis as was shown in Bactibase; however, this result is similar with the studies of Henderson (1992) and Bédard (2018), which reported that pediocin did not show activity against Staphylococcus aureus [3,32].…”
Section: Discussionsupporting
confidence: 86%